A Study to Assess the Knowledge, Attitude, and Practice Regarding Cervical Cancer among Women Attending Obstetrics and Gynecology Outpatient Department at MGM Hospital, Aurangabad with View to Develop Information Booklet - S. Sane, Vipulata (International Journal of Nursing Research, 2023)
Aim: The aim of the study was to assess the knowledge, attitude, and practice (KAP) regarding cervical cancer among women visiting obstetrics and gynecology outpatient department (OPD). Materials and Methods: A descriptive study was conducted at MGM hospital, Aurangabad. About 140 women attending obstetrics and gynecology OPD were included in the study by non-probability purposive sampling technique. Data were analyzed using descriptive and inferential statistics. Paired “t”-test was used to assess the KAP regarding cervical cancer among women visiting obstetrics and gynecology OPD. Results: The results showed that majority of women respondents in study lacked in their knowledge regarding cervical cancer 92 (62.71%), poor attitude 77 (55%), and poor practice 83 (59.28%), while negative correlation between knowledge and practice (0.011298), knowledge and attitude (–0.03), and practice and attitude (–0.14025) was found. Hence, the result showed that women were not only lacking in knowledge but also had poor attitude and very few practice regular screening for early detection of cervical cancer. Conclusion: The findings of the present study indicated that women need to be educated regarding cervical cancer and its screening tests as they lack knowledge and positive attitude toward cervical cancer, where many more are still unknown and hesitant for practicing screening tests for cervical cancer.